2007
DOI: 10.1002/app.24414
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behavior of epoxy composites containing reactive SiC nanoparticles

Abstract: The present article evaluated the sliding wear behaviors of epoxy and its composites filled with SiC nanoparticles. Polyglycidyl methacrylate (PGMA) and a copolymer of glycidyl methacrylate and styrene were grafted onto the nanoparticles as a measure of surface pretreatment, respectively. The grafted polymers were selected because the epoxide groups on PGMA would take part in the curing reaction of epoxy resin and covalently connect the nanoparticles with the matrix, while styrene acted as a copolymerized mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Accordingly, SiC nanoparticles (SiC np ) are attractive fillers for reinforcing polymers and for improving their wear properties [13][14][15][16][17][18]. Very recently, Mahfuz and coworkers studied the effect of SiC np additions on thermal and mechanical properties of epoxy resin [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, SiC nanoparticles (SiC np ) are attractive fillers for reinforcing polymers and for improving their wear properties [13][14][15][16][17][18]. Very recently, Mahfuz and coworkers studied the effect of SiC np additions on thermal and mechanical properties of epoxy resin [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, the effect of surface modification based on chemical interaction is more significant, as it provides stronger interaction between modifiers and nanoparticles. In our previous works, graft polymerization onto nanoparticles proved to be feasible in improving tribological behavior of polymer nanocomposites [15][16][17][18][19]. The grafted polymers changed the hydrophilic surface feature of the particles to hydrophobic and broke apart the nanoparticle agglomerates during polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…The modified silica nanoparticles have a strong interaction with EP according to entangling of molecular chains and chemical bonding between matrix and modified silica nanoparticles. Epoxy based composites incorporated with Al 2 O 3 nanoparticles [121,122], SiC nanoparticles [123,124] and Si 3 N 4 nanoparticles [125] which are modified by polymers have also been studied and it is evidenced that modified nanoparticles have a positive effect on wear resistance and friction reduction. The tribological behaviors of EP incorporated with surface modified silica nanoparticles and carbon fiber at the same time have been reported and it was shown that it is the synergy effect of nanoparticles and fibers that functions on the improvement of tribological properties of composites [126].…”
Section: Epoxy Resin (Ep) Biomaterialsmentioning
confidence: 98%